A comprehensive review on the co-occurrence of scurvy and anorexia nervosa - Cui, Sunny (Frontiers in Nutrition, 2024)
Scurvy, a rare disease resulting from vitamin C deficiency, can occur in individuals with restrictive eating disorders like anorexia nervosa (AN), leading to severe health complications. This review explores the complex relationship between scurvy and AN, highlighting the overlapping symptoms and challenges in diagnosis and treatment. Vitamin C is essential for collagen synthesis, immune function, and neurotransmitter production, and its deficiency manifests as fatigue, gingival bleeding, joint pain, and perifollicular hemorrhages. AN exacerbates these symptoms through extreme food restriction, causing severe nutritional deficiencies. Analyzing nine case reports, this review reveals that patients with co-occurring AN and scurvy often present with gastrointestinal, psychiatric, and dermatological symptoms. Treatment with vitamin C supplementation typically results in rapid symptom improvement. However, the malnutrition inherent in AN complicates the clinical picture, making timely diagnosis and intervention crucial. This review underscores the importance of a comprehensive, multidisciplinary approach to managing these conditions, emphasizing the need for early recognition and treatment to prevent severe complications. Future research should include a more diverse patient population to enhance understanding of the interplay between AN and scurvy, aiming to improve patient outcomes through tailored treatment strategies